Extended phylogenetic analysis of a new Israeli isolate of Brevicoryne brassicae virus (BrBV-IL) suggests taxonomic revision of the genus Iflavirus. Issue 1 (December 2016) - Luria, Neta; Reingold, Victoria; Lachman, Oded; Sela, Noa; Dombrovsky, Aviv
Abstract Background Brevicoryne brassicae virus (BrBV) is a positive-strand genomic RNA virus which is unassigned tentative member of the genusIflavirus . BrBv was first identified and characterized in the late 90's in the cabbage aphid in the United Kingdom (UK) (J Gen Virol 88:2590–2595, 2007) and was fully sequenced, using random amplification of encapsidated RNA. No other reports have been published demonstrating detection of this virus outside the UK. Findings A new isolate of the cabbage aphid virusBrevicoryne brassicae virus was identified fromBrevicoryne brassicae aphids growing on wild mustard plants (Sinapis arvensis ) in northern Israel. The virus genome was partially assembled from purified siRNA using the Illumina MiSeq Sequencing System with limited success. Combining classical viral RNA purification and RT-PCR amplification followed by traditional Sanger sequencing enabled obtaining the complete genomic sequence. The Israeli strain of BrBV shared 95 % nucleotide sequence identity with the BrBV found in the United Kingdom. Conclusions The detection of BrBV in Israel indicates a broader geographical distribution of the virus".